A MexR Mutation Which Confers Aztreonam Resistance to Pseudomonas aeruginosa - Ma, Zhenzhen; Xu, Congjuan; Zhang, Xinxin; Wang, Dan; Pan, Xiaolei; Liu, Huimin; Zhu, Guangbo; Bai, Fang; Cheng, Zhihui; Wu, Weihui; Jin, Yongxin (Frontiers in Microbiology, 2021)
Therapy for Pseudomonas aeruginosa infections is difficult due to its high natural and acquired antibiotic resistance. After colonization in the human hosts, P. aeruginosa commonly accumulates genomic mutations that confer the bacterium antibiotic resistance and better adaptations to the host environment. Deciphering the mechanisms of antibiotic resistance development in vivo may provide important insights into the design of effective combinatory antibiotic therapies to treat P. aeruginosa infections. In this work, we demonstrate a molecular mechanism by which an aztreonam-sensitive clinical isolate (CSP18) evolves to an aztreonam-resistant derivative (ARP36). RNAseq and genomic DNA re-sequencing were carried out to compare the global transcriptional profiles and in vivo evolutionary trajectories between these two isolates. The results demonstrated that hyper-expression of an efflux pump MexAB-OprM caused by a R70Q substitution in MexR, contributed to the increased resistance to aztreonam in the isolate ARP36. Simulation of mexR of ARP36 by gene editing in CSP18 conferred CSP18 an ARP36-like susceptibility to the aztreonam. The R70Q substitution prevented MexR from binding to the intergenic region between mexR and mexAB-oprM operon, with no impact on its dimerization. The presented experimental results demonstrate for the first time that the clinically relevant R70Q substitution in the MexR derepresses the expression of mexAB-oprM by compromising its binding capability.